Development of soil health card (SHC) using GIS technique - Sharma, R P; Singh, S K; Chandran, P; Chattaraj, S (Indian Farming, 2020)
Grid wise soil sampling with geographical coordinates, analyzing the samples with great precision and accuracy give better results to produce digital soil fertility maps and SHCs. GIS techniques can reduce the cost of SHC generation and helps in fastening the process of dissemination in farming community and advance farm inputs planning.